Determination of unit skin friction for pile in sand - Muhammat, Nurul Nadilah (2015)
The unit skin friction is difficult to assess. The method of installation of the pile and the pile material, as such, assume considerable significance as shall be seen hereafter. The choice of the unit skin friction formula depends on the soil type and the pile type. The consistency of unit skin friction value is depends on the unit weight of sand. Different types of sand will produce different values of unit skin friction. In this paper, a program of field and load testing tests for 2 bored piles with diameter varying from 600 mm to 750 mm constructed in Malaysian sand was conducted to measure the axial response of bored piles. The predicted unit skin friction were obtained from semi-empirical method suggested by Meyerhoff (1976), Reese and Wright (1977), and Tan et al. (1998). The measured unit skin friction value was estimated from back analysis of data obtained from pile load test. The results then were evaluated and compared. Based on the result obtained, the predicted unit skin friction of bored piles in dense sand will be higher than loose sand due to the roughness of the material itself. The measured unit skin friction obtained from back analysis of pile load test also provides the nearest value of unit skin friction to the predicted unit skin friction as suggested by Tan et al. (1998). It shows that the value can be considerably used for construction of bored piles in sand in Malaysia.